KUALITAS PEMERIKSAAN AUDITOR INTERNAL PEMERINTAH: STUDI PADA INSPEKTORAT KABUPATEN DAN KOTA DI ACEH - Muhammad Arfan; Darwanis Darwanis; Johan Wahyudi (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2021)
This study aims to test the influence of educational background, capacity, integrity, and conflict of role in the audit team on audit quality of government internal auditors in Aceh. This study is a hypothesis testing research. The population were 299 auditors working for the inspectorate's office of regency and city in Aceh. Then, by using Slovin formula and proportionate stratified random sampling, the samples were 92 auditors. The data used were primary data for the year 2020 collected through a questionnaire on a one-stage time horizon. The analysis method used multiple linear regression. The result showed that educational background had no influence, while capacity, integrity, and conflict of role in the audit team partially had an influence on audit quality of government internal auditors in Aceh. Limitation of this study was questionaires were sent via internet by using google form, so that not all questionnaires were returned by the respondents. In addition, the time for returning the questionnaires was different between the respondents and some even returned them too long. The implications of this study is that it can help the government, especially the government of regency and city in Aceh, to be able to improve the audit quality of internal auditors by taking into account the factors that influence it, in particular the capacity and integrity of internal auditors.